2009
DOI: 10.2164/jandrol.108.005967
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Palpable Varicocele in Infertile Men: A Meta‐analysis to Define the Best Technique

Abstract: To date, there have been no randomized, controlled, prospective clinical studies that compare various techniques to describe the best method for the treatment of varicocele in infertile men. This meta-analysis aims to address the best treatment modality for palpable varicocele in infertile men. A MEDLINE search was performed for articles published between January 1980 and April 2008, and we analyzed 36 studies reporting postoperative spontaneous pregnancy rates and/or complication rates after varicocele repair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
274
1
27

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 348 publications
(315 citation statements)
references
References 62 publications
13
274
1
27
Order By: Relevance
“…Percutaneous embolization offers a rapid recovery and can give good success rate, but the technique demands interventional radiologic expertise and has potential serious complications, including vascular perforation, coil migration, thrombosis of pampiniform plexus [64,65]. Lima et al have recently pioneered natural orifice transluminal endoscopic surgical procedures (NOTES) to perform varicocelectomy as an important minimally invasive approach [66,67].…”
Section: Treatment Options and Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…Percutaneous embolization offers a rapid recovery and can give good success rate, but the technique demands interventional radiologic expertise and has potential serious complications, including vascular perforation, coil migration, thrombosis of pampiniform plexus [64,65]. Lima et al have recently pioneered natural orifice transluminal endoscopic surgical procedures (NOTES) to perform varicocelectomy as an important minimally invasive approach [66,67].…”
Section: Treatment Options and Outcomesmentioning
confidence: 99%
“…However, there is no objective data to substantiate a clear advantage of one over the other. Cayan et al [65] in a systematic review involving 4,473 men aimed to define the best modality of treatment in palpable varicocele in infertile men. The authors concluded that open inguinal or subinguinal artery and lymphatic sparing microsurgical techniques resulted in higher spontaneous pregnancy rate, fewer recurrence and complications compared to laparoscopic, radiologic embolisation, macroscopic inguinal or retroperitoneal procedures.…”
Section: Treatment Options and Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…The inguinal (Ivanissevich) and subinguinal approaches also allow the ligation of the external spermatic and cremasteric veins that may contribute to the varicocele. A recent systematic review including 4,473 infertile individuals was performed to define the best treatment modality for varicocele [53]. The authors concluded that open microsurgical inguinal or subinguinal varicocelectomy techniques resulted in higher spontaneous pregnancy rates and fewer recurrences and postoperative complications than laparoscopic, radiologic embolization and macroscopic inguinal or retroperitoneal varicocelectomy techniques (Fig.…”
Section: Microsurgical Repair Of Clinical Varicocelementioning
confidence: 99%
“…Нарушение фертиль-ности при варикоцеле отмечается в 20-80% случаев, а среди пациентов, страдающих бесплодием, варико-целе выявлено у 30-40%. Связь варикоцеле с бес-e-mail: rasulovjamshid@mail.ru плодием явилась основной причиной включения данной патологии в число программ, разрабатывае-мых ВОЗ [2,5,7].Различают непрямые и прямые комбинирован-ные способы хирургического лечения варикоцеле. Прямые способы операции на венах семенного ка- Цель исследования -улучшить результаты хирургического лечения варикоцеле путем разработки способов с использованием микрохирургической техники.…”
unclassified